Visual Analysis Plus Hierarchical Linear Model Regressions: Morphosyntax Intervention with Deaf-and-Hard-of-Hearing Students. (May 2022) - Hasko, Janna; Rivera, M. Christina; Erbacher, Monica K.; Antia, Shirin D.
We conducted a pilot study using intentional teaching strategies with specially designed materials to improve accuracy and production of targeted English morphosyntax structures with six deaf and hard-of-hearing students (kindergarten to first grade). A multiple baseline single-case research design (SCRD) consisting of 20-minute sessions four times per week for the duration of a school year was implemented to determine the effect of the supplemental syntax curriculum. The data were inconsistent and highly variable. Visual analyses were problematic; therefore, hierarchical linear model (HLM) regression analyses were conducted with the time series SCRD data as an additional analysis. HLM regression analyses were used to interpret data that might otherwise be overlooked in SCRDs to provide specific values for the rate students were learning during the intervention phase of the study. This pilot study demonstrates that the syntax intervention produces promising results when data that are too messy for visual analysis are analyzed with HLM.